O investimento público enquanto vetor da qualidade do ensino - Bomfim, Daiesse Quênia Jaala Santos (2021)
Education is a social right that contributes to the formation of the individual and, consequently, provides the development of a country. Although it is not a sufficient factor and considered in isolation, adequate financing of educational policy is a necessary condition for the universalization of the right to quality public education. Thus, alongside the issue of financing, it is necessary to discuss the quality of education in the country, from the perspective of the necessary inputs to ensure an effective teaching-learning process. That said, this research aimed to delineate the congruence between public investment and the search for quality in education in Brazil, presenting the concept of Cost Student Quality, whose methodology encompasses, among others, the remuneration and continued training of teachers, equipment and adequate infrastructure and acquisition of teaching material. Using a brief historical contextualization of education financing, it is possible to see an advance in the systematic of investments in the educational sector, especially regarding the institutionalization of accounting funds, mechanisms for linking resources to public education. However, even under the guise of the idea of cooperative federalism, the allocation of resources in the educational sector is a complex process, in view of the relevant regional disparities in the country and has as a major challenge the promotion of equity in the National Education System. Thus, it is concluded that the need for structural changes in Brazilian educational policy, in particular the increase in public funding, should reflect on the reconstitution of the social pact, emphasizing the quality of public education and the equalization of educational opportunities.